Evaluation of explanation of the BASNEF model on smoking waterpipe among the students one of the medical universities located in the south of Iran - Mohammad Hossein kaveh; Alireza Jafari2; Sareh Keshavarzi; Victoria Momenabadi; Mostafa Taheri; Farzaneh Dehbozorgi; Tal-at Motazedian (Iranian Association of Health Education and Health Promotion, 2019)
Background and Objective: The current evidences have indicated that the prevalence of smoking cigarette and waterpipe has an ascending trend among the university students since their first year of study. The present study aimed to evaluation of explanation of the BASNEF model on smoking waterpipe among the university students. Materials and Methods: This cross-sectional study was conducted on 462 students selected by proportional stratified random sampling. The study data were collected using demographic questionnaire and researcher-made questionnaire based on the "BASNEF" model. The collected data were then entered into the SPSS statistical software (v. 19) and analyzed using descriptive statistics, Pearsons correlation coefficient and Regression analysis. Results: The prevalence rates of smoking cigarette and waterpipe were 11.7% and 16.6%, respectively. The results showed no significant difference in using cigarette or waterpipe by gender(p<0.01). The participants' mean scores of attitudes, subjective norms, and enabling factors were 72.96±14.95, 21.51±5.31, and 19.1±4.04, respectively, regarding behavioral intent, 35.28% of consumers said they would never stop smoking waterpipe, and only 4.32% said they were more likely to quit smoking waterpipe within the next month. conclusion: Considering the prevalence of smoking waterpipe and cigarette among the students and the relatively inappropriate attitudes, subjective norms, and enabling factors to quit smoking, educational interventions based on interpersonal models to prevent or quit high-risk behaviors are suggested.